The role of α2‐adrenergic receptors in hypertensive preeclampsia: A hypothesis. (27th November 2018) - Maaliki, Dina; Issa, Khodr; Al Shehabi, Tuqa; El‐Yazbi, Ahmed; Eid, Ali H.
Abstract: Preeclampsia, a major disorder of human pregnancy, manifests as persistent hypertension and proteinuria presenting after 20 weeks of pregnancy. Multiple systemic symptoms might be associated with preeclampsia including thrombocytopenia, liver impairment, pulmonary edema, and cerebral disturbances. However, vascular dysfunction remains the core pathological driver of preeclampsia. Defective placental implantation followed by dysfunctional placental spiral artery development promotes a hypoxic environment. Massive endothelial dysfunction characterized by reduced vasodilation, augmented vasoconstriction, and increased vascular permeability and inflammation ensues. Interestingly, the same signaling and inflammatory pathways implicated in preeclampsia appear to be shared with other vascular disorders involving alteration of α2 ‐AR function. The role of α2 ‐ARs in the regulation of microcirculatory function has long been recognized, thus raising the question of whether they are involved in the pathogenesis of vascular dysfunction in preeclampsia. Here, we review possible interplay between signaling and inflammatory pathways common to preeclampsia and α2 ‐AR function/regulation. We speculate on the potential contribution of these receptors to the observed phenotype and the potential role for their pharmacological modulators as therapeutic interventions with preeclampsia.